Development of Graphene‐Based Materials in Bone Tissue Engineaering. Issue 2 (2nd December 2021) - Pan, Xiaoling; Cheng, Delin; Ruan, Changshun; Hong, Yonglong; Lin, Cheng
Abstract: Bone regeneration‐related graphene‐based materials (bGBMs) are increasingly attracting attention in tissue engineering due to their special physical and chemical properties. The purpose of this review is to quantitatively analyze mass academic literature in the field of bGBMs through scientometrics software CiteSpace, to demonstrate the rules and trends of bGBMs, thus to analyze and summarize the mechanisms behind the rules, and to provide clues for future research. First, the research status, hotspots, and frontiers of bGBMs are analyzed in an intuitively and vividly visualized way. Next, the extracted important subjects such as fabrication techniques, cytotoxicity, biodegradability, and osteoinductivity of bGBMs are presented, and the different mechanisms, in turn, are also discussed. Finally, photothermal therapy, which is considered an emerging area of application of bGBMs, is also presented. Based on this approach, this work finds that different studies report differing opinions on the biological properties of bGBMS due to the lack of consistency of GBMs preparation. Therefore, it is necessary to establish more standards in fabrication, characterization, and testing for bGBMs to further promote scientific progress and clinical translation. Abstract : Herein, scientometrics is used to make a quantitative analysis of academic literature on bone regeneration‐related graphene‐based materials (bGBMs), to visually display the relevant research rules and trends. The fabrication techniques, cytotoxicity, biodegradability, osteoinductivity, photothermal properties, and thus the underlying mechanisms of bGBMs are discussed. Even with all these advantages, the lack of standardization of bGBM preparation technology remains a problem to be solved.